Nemaline body myopathy caused by a novel mutation in troponin T1 (TNNT1). Issue 4 (3rd September 2015) - Abdulhaq, Ulla Najwa; Daana, Mohannad; Dor, Talia; Fellig, Yakov; Eylon, Sharon; Schuelke, Markus; Shaag, Avraham; Elpeleg, Orly; Edvardson, Simon
ABSTRACT: Introduction : Nemaline myopathy is a rare disorder characterized by skeletal muscle weakness of varying severity and onset, with the presence of nemaline rods on muscle biopsy. Congenital nemaline body myopathy due to mutations in TNNT1 has hitherto only been described as a result of a single founder mutation in patients of Amish origin and in 2 other individuals with different recessive mutations. Methods : Autozygosity mapping and whole exome sequencing were applied after we identified 9 Palestinian patients from 7 unrelated families who have nemaline myopathy. Results : All patients were homozygous for a novel complex rearrangement of the TNNT1 gene (c.574_577delinsTAGTGCTGT | NM_003283) leading to C‐terminal truncation of the protein (p.L203* | NP_003274.3). Their clinical course was remarkable for early respiratory failure and striking stiffness of the cervical spine. Conclusions : This report exemplifies the utility of combining autozygosity mapping and whole exome sequencing and expands the phenotype associated with TNNT1 mutations. Muscle Nerve 53 : 564–569, 2016